1999
DOI: 10.2307/3434339
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimmunotoxicology: Humoral Assessment of Neurotoxicity and Autoimmune Mechanisms

Abstract: The interactions between the nervous and immune systems have been recognized in the development of neurodegenerative disease. This can be exploited through detection of the immune response to autoantigens in assessing the neurotoxicity of environmental chemicals. To test this hypothesis, the following questions were addressed. a) Are autoantibodies to nervous system (NS) antigens detected in populations exposed to environmental or occupational chemicals? In sera of male workers exposed to lead or mercury, auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
0
14
2
Order By: Relevance
“…This is not surprising as it has been shown that chemical-induced alterations of one biological system can affect normal functioning of another (El-Fawal et al, 1999), and this is especially true when two organ systems (e.g., the immune and nervous systems) are known to share common receptors/ligands and act to cross-regulate each other (Lawrence and Kim, 2000). In this latter scenario, a variety of immune cell types from both mammals and fish have demonstrated 5-HT receptors and the 5-HT reuptake transporter (5-HTT) (Khan and Deschaux, 1997;Lawrence and Kim, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This is not surprising as it has been shown that chemical-induced alterations of one biological system can affect normal functioning of another (El-Fawal et al, 1999), and this is especially true when two organ systems (e.g., the immune and nervous systems) are known to share common receptors/ligands and act to cross-regulate each other (Lawrence and Kim, 2000). In this latter scenario, a variety of immune cell types from both mammals and fish have demonstrated 5-HT receptors and the 5-HT reuptake transporter (5-HTT) (Khan and Deschaux, 1997;Lawrence and Kim, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the antibodies to antineurofilament 68-kd protein are virtually nonexistent in autistic children, who primarily harbor antibodies to myelin basic protein [8] but sometimes also have antibodies to glial filament protein and neuron-axonal filament 200-kd protein [11]. Furthermore, it should be clearly pointed out that the mercuryexposed industrial workers very seldom harbor antibodies to myelin basic protein or neuron-axonal filament 200-kd protein [3]. Indeed, this is an important distinction between the mercury-exposed autoimmunity and the idiopathic autoimmunity in autism.…”
Section: Resultsmentioning
confidence: 90%
“…Autistic children are not known to have the nephrotic syndrome and, as described here, they had normal titers of antilaminin antibodies, suggesting the absence of a mercury-induced autoimmune reaction in autistic children. Mercury exposure in industrial workers induces antibodies to neural antigens, mainly the neurofilament 68-kd protein [3]. In contrast, the antibodies to antineurofilament 68-kd protein are virtually nonexistent in autistic children, who primarily harbor antibodies to myelin basic protein [8] but sometimes also have antibodies to glial filament protein and neuron-axonal filament 200-kd protein [11].…”
Section: Resultsmentioning
confidence: 96%
“…Lead's ability to influence the risk of autoimmunity is not always associated with a rigorous shift to T h 2 responses [35]. Some studies have described a more complicated sequence of events, in which the type-1 cytokine IFN-g is also linked with heavy metal-induced autoimmunity, which may also be associated to kidney pathologies [36].…”
Section: Pb-induced Oxidative Stressmentioning
confidence: 99%